Various robust search methods in a Hungarian speech recognition system - Gosztolya, Gábor; Kocsor, András; Tóth, László; Felföldi, László (Acta Cybernetica, 2003)
This work focuses on the search aspect of speech recognition. We describe some standard algorithms such as stack decoding, multi-stack decoding, the Viterbi beam search and an A* heuristic, then present improvements on these search methods. Finally we compare the performance of each algorithm, grading them according to their performance. We will show that our improvements can outperform the standard methods.